Oxygen defective titanate nanotubes induced by iron deposition for enhanced peroxymonosulfate activation and acetaminophen degradation: Mechanisms, water chemistry effects, and theoretical calculation - Ma, Jun; Long Chen; Yue Liu; Tianyuan Xu; Ji, Haodong; Duan, Jun; Fengbin Sun; Liu, Wen (Journal of Hazardous Materials, 2021)
The large consumption of acetaminophen (APAP) worldwide and unsatisfactory treatment efficiencies by conventional wastewater treatment processes give rise to the seeking of new technology for its effective removal. Herein, we proposed a facile one-step hydrothermal method to synthesize defective iron deposited titanate nanotubes (Fe/TNTs) for peroxymonosulfate (PMS) activation and APAP degradation. The retarded first-order reaction rate of APAP degradation by Fe/TNTs was 5.1 times higher than that of neat TNTs. Characterizations indicated iron deposition effectively induced oxygen vacancies and Ti3+, facilitating the electrical conductivity and PMS binding affinity of Fe/TNTs. Besides, oxygen vacancies could act as an electron mediator through PMS activation by iron. Moreover, the formation of Fe–O–Ti bond facilitated the synergistic redox coupling between Fe and Ti, further enhancing the PMS activation. SO4•− was the major radical, causing C–N bond cleavage and decreasing the overall toxicity. In contrast, APAP degradation by neat TNTs-PMS system mainly works through nonradical reaction. The Fe/TNTs activated PMS showed desired APAP removal under mild water chemistry conditions and good reusability. This work is expected to expand the potential application of titanate nanomaterials for PMS activation, and shed light on facile synthesis of oxygen defective materials for sulfate-radical-based advanced oxidation processes.
Keywords: Acetaminophen; Density functional theory; Oxygen vacancies; Peroxymonosulfate; Titanate nanotubes